Clonal Hematopoiesis of Indeterminate Potential is Associated with Acute Kidney Injury. - Vlasschaert, Caitlyn; Robinson-Cohen, Cassianne; Kestenbaum, Bryan; Silver, Samuel A; Chen, Jian-Chun; Akwo, Elvis; Bhatraju, Pavan K; Zhang, Ming-Zhi; Cao, Shirong; Jiang, Ming; Wang, Yinqiu; Niu, Aolei; et al. (medRxiv, 2023)
Age is a predominant risk factor for acute kidney injury (AKI), yet the biological mechanisms underlying this risk are largely unknown and to date no genetic mechanisms for AKI have been established. Clonal hematopoiesis of indeterminate potential (CHIP) is a recently recognized biological mechanism conferring risk of several chronic aging diseases including cardiovascular disease, pulmonary disease and liver disease. In CHIP, blood stem cells acquire mutations in myeloid cancer driver genes such as and and the myeloid progeny of these mutated cells contribute to end-organ damage through inflammatory dysregulation. We sought to establish whether CHIP causes acute kidney injury (AKI). To address this question, we first evaluated associations with incident AKI events in three population-based epidemiology cohorts (N = 442,153). We found that CHIP was associated with a greater risk of AKI (adjusted HR 1.26, 95% CI: 1.19-1.34, p<0.0001), which was more pronounced in patients with AKI requiring dialysis (adjusted HR 1.65, 95% CI: 1.24-2.20, p=0.001). The risk was particularly high in the subset of individuals where CHIP was driven by mutations in genes other than (HR: 1.49, 95% CI: 1.37-1.61, p<0.0001). We then examined the association between CHIP and recovery from AKI in the ASSESS-AKI cohort and identified that non- CHIP was more common among those with a non-resolving pattern of injury (HR 2.3, 95% CI: 1.14-4.64, p = 0.03). To gain mechanistic insight, we evaluated the role of -CHIP to AKI in ischemia-reperfusion injury (IRI) and unilateral ureteral obstruction (UUO) mouse models. In both models, we observed more severe AKI and greater post-AKI kidney fibrosis in -CHIP mice. Kidney macrophage infiltration was markedly increased in -CHIP mice and -CHIP mutant renal macrophages displayed greater pro-inflammatory responses. In summary, this work establishes CHIP as a genetic mechanism conferring risk of AKI and impaired kidney function recovery following AKI via an aberrant inflammatory response in CHIP derived renal macrophages.

Late-life plasma proteins associated with prevalent and incident frailty: A proteomic analysis. - Liu, Fangyu; Austin, Thomas R; Schrack, Jennifer A; Chen, Jingsha; Walston, Jeremy; Mathias, Rasika A; Grams, Morgan; Odden, Michelle C; Newman, Anne; Psaty, Bruce M; Ramonfaur, Diego; Shah, Amil M; et al. (Aging Cell, 2023)
Proteomic approaches have unique advantages in the identification of biological pathways that influence physical frailty, a multifactorial geriatric syndrome predictive of adverse health outcomes in older adults. To date, proteomic studies of frailty are scarce, and few evaluated prefrailty as a separate state or examined predictors of incident frailty. Using plasma proteins measured by 4955 SOMAmers in the Atherosclerosis Risk in Community study, we identified 134 and 179 proteins cross-sectionally associated with prefrailty and frailty, respectively, after Bonferroni correction (p < 1 × 10 ) among 3838 older adults aged ≥65 years, adjusting for demographic and physiologic factors and chronic diseases. Among them, 23 (17%) and 82 (46%) were replicated in the Cardiovascular Health Study using the same models (FDR p < 0.05). Notably, higher odds of prefrailty and frailty were observed with higher levels of growth differentiation factor 15 (GDF15; p  = 1 × 10 , p  = 2 × 10 ), transgelin (TAGLN; p  = 2 × 10 , p  = 6 × 10 ), and insulin-like growth factor-binding protein 2 (IGFBP2; p  = 5 × 10 , p  = 1 × 10 ) and with a lower level of growth hormone receptor (GHR, p  = 3 × 10 , p  = 2 × 10 ). Longitudinally, we identified 4 proteins associated with incident frailty (p < 1 × 10 ). Higher levels of triggering receptor expressed on myeloid cells 1 (TREM1), TAGLN, and heart and adipocyte fatty-acid binding proteins predicted incident frailty. Differentially regulated proteins were enriched in pathways and upstream regulators related to lipid metabolism, angiogenesis, inflammation, and cell senescence. Our findings provide a set of plasma proteins and biological mechanisms that were dysregulated in both the prodromal and the clinical stage of frailty, offering new insights into frailty etiology and targets for intervention.